Radiotherapeutic Strategies in the Management of Low-Risk Prostate Cancer - Kevin S. Choe; Stanley L. Liauw (The Scientific World Journal)
Prostate cancer is the most common nonskin malignancy among men in the United States. Since the introduction of screening with prostate-specific antigen (PSA), most patients are being diagnosed at an early stage with low-risk disease. For men with low-risk prostate cancer, there exists an array of radiotherapeutic strategies that are effective and well tolerated, such as external-beam radiotherapy and brachytherapy. In recent years, there have been tremendous advances in the field of radiation oncology that have transformed the way radiation is used to treat prostate cancer, such as intensity-modulated radiotherapy, image-guided radiotherapy, and stereotactic radiotherapy. It is now feasible to deliver high doses of radiation to the target volume with improved precision and spare more of the neighboring tissues from potentially damaging radiation. Disease outcomes are generally excellent in low-risk prostate cancer. Improvements are expected with further integration of innovative technologies in radiation delivery, tumor imaging, and target localization.